Bottlenecks to clinical translation of direct brain-computer interfaces - Serruya, Mijail D. (Frontiers in Systems Neuroscience, 2014)
Despite several decades of research into novel brain-implantable devices to treat a range of diseases, only two- cochlear implants for sensorineural hearing loss and deep brain stimulation for movement disorders- have yielded any appreciable clinical benefit. Obstacles to translation include technical factors (e.g., signal loss due to gliosis or micromotion), lack of awareness of current clinical options for patients that the new therapy must outperform, traversing between federal and corporate funding needed to support clinical trials, and insufficient management expertise. This commentary reviews these obstacles preventing the translation of promising new neurotechnologies into clinical application and suggests some principles that interdisciplinary teams in academia and industry could adopt to enhance their chances of success.